APPLICATION OF NATIONAL EMBROIDERY IN MODERN CLOTHING (American Journal of Interdisciplinary Research and Development, 2022)
Embroidery, as a folk craft widely inherited by our country, has experienced thousands of years of cultural accumulation and precipitation, and has a very high artistic achievement. Under the background of economic and cultural development, traditional embroidery has formed a unique and complete art system, which has a high reference value for the application and development of fashion design. The article dwells into details about the application of national embroidery in modern clothing.